2017
DOI: 10.1093/cvr/cvx122
|View full text |Cite
|
Sign up to set email alerts
|

The expression of the rare caveolin-3 variant T78M alters cardiac ion channels function and membrane excitability

Abstract: AimsCaveolinopathies are a family of genetic disorders arising from alterations of the caveolin-3 (cav-3) gene. The T78M cav-3 variant has been associated with both skeletal and cardiac muscle pathologies but its functional contribution, especially to cardiac diseases, is still controversial. Here, we evaluated the effect of the T78M cav-3 variant on cardiac ion channel function and membrane excitability.Methods and resultsWe transfected either the wild type (WT) or T78M cav-3 in caveolin-1 knock-out mouse emb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…In particular, it has been characterized as a variant of unknown or benign significance after it has been found in healthy individuals with frequencies comparable to cases with long QT syndrome [ 55 , 56 ]. Even though this variant has been found also in the patient’s asymptomatic father, we ascribe this to a possible concerted action with another yet unidentified variant that predisposes to the specific phenotypic characteristics, as it has been previously suggested for the role of p.Thr78Met CAV3 in cardiac diseases [ 57 ].…”
Section: Discussionmentioning
confidence: 62%
“…In particular, it has been characterized as a variant of unknown or benign significance after it has been found in healthy individuals with frequencies comparable to cases with long QT syndrome [ 55 , 56 ]. Even though this variant has been found also in the patient’s asymptomatic father, we ascribe this to a possible concerted action with another yet unidentified variant that predisposes to the specific phenotypic characteristics, as it has been previously suggested for the role of p.Thr78Met CAV3 in cardiac diseases [ 57 ].…”
Section: Discussionmentioning
confidence: 62%
“…Caveolin 3 (Cav3) is a caveolin family member protein expressed in cell types that act as a scaffolding protein for the organization and concentration of certain caveolin-interacting molecules. Mutations in this gene is attributed to lead to Limb-Girdle muscular dystrophy type-1C (LGMD-1C), hyperCKemia, or rippling muscle disease (RMD) (39). It has been reported that Cav3 expression in mice is primarily in heart and skeletal muscle (40).…”
Section: Resultsmentioning
confidence: 99%
“…Cav-3, the integral membrane protein that is essential in formation of caveolae (Figures 1 , 2 ), is also linked with SND ( Lang et al, 2016 ; Campostrini et al, 2017 ). As discussed in the previous sections, Cav-3 is involved in the regulation of multiple ion channels and transporters, including those involved in pacemaking.…”
Section: Snd and Scaffolding Proteinsmentioning
confidence: 99%
“…Cav-3 F97C and S141R mutations have been linked to the long QT type 9 inherited arrhythmia syndrome (LQT9) causing AP duration prolongation which had been attributed to an increase in late Na + current ( Vatta et al, 2006 ). In spontaneously beating neonatal cardiomyocytes, the expression of the T78M mutation in CAV3 gene significantly increased AP peak-to-peak variability without altering neither the mean rate nor the maximum diastolic potential ( Campostrini et al, 2017 ) and was associated with a positive shift of activation of HCN4 channels, in a dominant way. The authors also identified a small cohort of patients with supraventricular arrhythmias including sinus tachycardia, bradycardia, and atrial fibrillation where the T78M Cav-3 variant is more frequent than in the general population.…”
Section: Snd and Scaffolding Proteinsmentioning
confidence: 99%